Mainstreaming the special child implications on collection development strategies of Quezon City libraries for children and young adults with down's syndrome - Agcambot, Fraulein A.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This study is a survey of the existing educational institutions which cater to the information needs of children and young adults with Down's syndrome. Specifically, the study focuses on the collection development practices of the libraries/resource centers of these institutions. At least five institutions active in the concerns of the developmentally disadvantaged have been identified, namely: the Cupertino Center for Special Children, the St. John Ma. Vianney Foundation, Inc., the Montessori Children's House, the Discovery Preschool, and the Down Syndrome Association of the Philippines. Among the significant findings include the positive perception of librarians or teacher-librarians of these institutions towards the potential for education of children and young adults with Down's syndrome. In terms of the collection development strategies of these institutions, both past and current efforts are geared towards the acquisition of materials that come in various formats: books, educational toys, and audio-visual materials. Educational toys and audio-visual materials have been found to be very useful in the educational process of children and young adults afflicted with Down's syndrome. These materials are a common sight among the libraries of the surveyed institutions.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Children's libraries -- Collection development -- Philippines -- Quezon City; Libraries and mentally handicapped children -- Philippines -- Quezon City